2011
DOI: 10.2174/092986711797287575
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Immunological and Three-Dimensional Analysis of Chemically Synthesised Sporozoite Peptides as Components of a Fully-Effective Antimalarial Vaccine

Abstract: Our ongoing search for a fully-effective vaccine against the Plasmodium falciparum parasite (causing the most lethal form of human malaria) has been focused on identifying and characterising proteins' amino acid sequences (high activity binding peptides or HABPs) involved in parasite invasion of red blood cells (RBC) by the merozoite and hepatocytes by the sporozoite. Many such merozoite HABPs have been recognised and molecularly and structurally characterised; however, native HABPs are immunologically silent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 241 publications
(520 reference statements)
0
25
0
1
Order By: Relevance
“…A significant amount of HABPs have been identified in most P. falciparum proteins participating in Spz and Mz invasion of their respective target cells (Rodriguez et al, ; Curtidor, Vanegas, Alba, & Patarroyo, ). After HABPs have undergone a series of chemical modifications and structural and immunological studies, they have been able to induce a strong protection‐inducing immune response in experimental challenge in a non‐human primate animal model (Curtidor, Patarroyo, & Patarroyo, ).…”
Section: Resultsmentioning
confidence: 99%
“…A significant amount of HABPs have been identified in most P. falciparum proteins participating in Spz and Mz invasion of their respective target cells (Rodriguez et al, ; Curtidor, Vanegas, Alba, & Patarroyo, ). After HABPs have undergone a series of chemical modifications and structural and immunological studies, they have been able to induce a strong protection‐inducing immune response in experimental challenge in a non‐human primate animal model (Curtidor, Patarroyo, & Patarroyo, ).…”
Section: Resultsmentioning
confidence: 99%
“…A group of Colombian P. falciparum isolates were adapted to continuous in vitro culture more than 30 years ago; the falciparum Colombia Bogotá 2 (FCB2) strain (an in vitro culture-adapted isolate from Colombia's Eastern Plains) from that group was described as having sexual differentiation capability [24]. This strain has been used for antigen analysis when developing an anti-malarial vaccine and in studies of the human immune response against the parasite [25][26][27]. This strain has been maintained in in vitro continuous culture since then but it was not known if it conserved its sexual differentiation ability or whether sexual forms could evolve to mature forms and infect local Anopheles species [24].…”
Section: Introductionmentioning
confidence: 99%
“…The Fundación Instituto de Inmunología de Colombia (FIDIC) has thoroughly demonstrated the feasibility of a chemically synthesised, multistage, multiantigen, minimum subunit-based (~20 amino acid-long peptide) vaccine by following a completely functional approach [4,5]. This has led to ascertaining that peptides derived from the main proteins participating in merozoite (Mrz) invasion of RBCs [6] specifically bind to human RBCs and that sporozoites (Spz) invading hepatic cells [7,8] bind to the HepG2 hepatocellular carcinoma cell line [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This study thus used a murine model for evaluating the immunogenicity, local toxicity, and systemic toxicity [34][35][36][37][38] of a mixture of 23 IMPIPS. These were derived from the main P. falciparum Spz (circumsporozoite protein 1 (CSP-1), thrombospondin-related anonymous protein (TRAP), sporozoite threonine and asparagine-rich protein (STARP), sporozoite microneme proteins essential for cell traversal (SPECT-1 and SPECT-2), cell-traversal protein for ookinetes and sporozoites (CelTOS), and sporozoite invasionassociated protein 1 and 2 (SIAP-1 and SIAP-2)) [9,11,39,40], as well as Mrz proteins (apical membrane antigen-1 (AMA-1), erythrocyte-binding protein 175 (EBA-175), erythrocyte-binding protein 140 (EBA-140), serine repeat antigen (SERA-5), merozoite surface protein-1 (MSP-1), and histidine-rich protein II (HRP-II)) [10,39,40]. Previous studies testing these peptides individually have shown that the antibodies induced were able to recognise the original template protein when expressed as a recombinant (Supplementary Table 1).…”
Section: Introductionmentioning
confidence: 99%